Analysis of switched mode power supply (SMPS) with energy saving requirement - Ang, Swee Liew
This project aims to minimize the total power consumption (<1W) in an idle state (standby mode). This will be evaluated through a number of options in switchmode technology. Thus, prototype switchmode power supply solutions will be compared to the existing power supply solutions found in domestic electronic equipments, and the analysis results successfully helped confirm the operation of the prototype device and investigate its uncompromised performance. In addition, it provides useful information for next generation product development.